Methodology of Examination of Patients with Osteoarthritis and Aseptic Necrosis of Hip and Knee Joints when Using Regenerative Interventional Technologies - Strafun, S.S.; Holiuk, Ye.L. (TERRA ORTHOPAEDICA, 2023)
Background. Diagnosis of osteoarthritis of the hip and knee joints, as of today, would seem to be a well-studied issue. Radiography, magnetic resonance imaging, ultrasonography - each of these methods makes it possible to make a diagnosis. At the same time, the use of new methods of treatment of osteoarthritis requires new approaches to its diagnosis. Objective: to develop a methodology for examining patients with osteoarthritis and aseptic necrosis of the hip and knee joints during treatment with regenerative technologies. Material and Methods. The material for the study was case histories of 233 patients with osteoarthritis and 58 patients with osteoarthritis of the hip and knee joints. Clinical, laboratory, and instrumental research methods were used. Results. The methodology of clinical examination of patients when using regenerative technologies is based on filling out quality of life questionnaires. A feature of the methodology of laboratory examination of patients with osteoarthritis and aseptic necrosis of the hip and knee joints when using regenerative technologies is oncological screening in the case of the use of biotechnological products containing MSCs, with the determination of epigenetic markers of the risk of oncogenesis in the form of miRNA. Conclusions. The methodology of the instrumental examination of patients with osteoarthritis is as follows: the key is an X-ray examination with the establishment of the stage of osteoarthritis according to the Kellgren-Lawrence classification and the subsequent ultrasound and MRI examination in order to assess the extent of damage to the soft tissues of the hip and knee joints, subchondral bone and paraarticular structures. In patients with aseptic necrosis of the hip and knee joints, when using regenerative technologies, the key is an MRI study followed by X-ray and ultrasound examination.